1970
DOI: 10.3126/njms.v1i1.5797
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Body in the Esophagus-Comparison Between Adult and Pediatric Population

Abstract: Background: Foreign body (FB) impaction in the esophagus is a common emergency in all age groups. In the children coins are the commonest foreign bodies while bones have been found as the commonest in adults. Methods: This is a retrospective study comparing FB in the esophagus in adult and pediatric population between June 2007 and May 2010 in Manipal Teaching Hospital, Pokhara, Nepal. Most of the patients underwent rigid esophagoscopy and FB removal; few were removed under anesthesia by the anesthesiologists.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 5 publications
0
13
0
2
Order By: Relevance
“…al compared esophageal foreign body in pediatric and adult population the result of which showed that out of total cases of foreign body impaction, 44.4% patients were children and 55.5% were adults. Coin was the most common foreign body in the pediatric population (82.1%) whereas bones were the commonest ones (91.4%) in adults 5 . The study concluded that coins being the commonest foreign bodies in children were relatively easier to remove due to their higher location and less chances of trauma where as in the adults, bones being the commonest foreign body were diffi cult to remove due to the lower location and increased chances of trauma 5 .…”
Section: Discussionmentioning
confidence: 99%
“…al compared esophageal foreign body in pediatric and adult population the result of which showed that out of total cases of foreign body impaction, 44.4% patients were children and 55.5% were adults. Coin was the most common foreign body in the pediatric population (82.1%) whereas bones were the commonest ones (91.4%) in adults 5 . The study concluded that coins being the commonest foreign bodies in children were relatively easier to remove due to their higher location and less chances of trauma where as in the adults, bones being the commonest foreign body were diffi cult to remove due to the lower location and increased chances of trauma 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Erişkinlerde özofagus yabancı cisimlerinin çoğunluğunun torasik özofagusa yerleştiği rapor edilmiştir. [4,13] Slaone ve arkadaşları ise 150 hastadan elde ettikleri sonuçlarda yabancı cisimlerin erişkinler-de %53 oranında diyafragmatik özofagusa yerleştiğini bildirmiştir. [4,14] Aynı çalışmada erişkinlerde buldukları bu sonucun özofagus hastalıklarının en sık lokalize olduğu yer olması açısından da uyumlu olabileceği dile getirilmiştir.…”
Section: Gereç Ve Yöntemunclassified
“…These patients are at risk of complications from expectant management of foreign body ingestion. 3,4 Additionaly, the literature contains fewer reports on this topic that focus on psyciatric issues involved.…”
Section: Introductionmentioning
confidence: 99%
“…Children having the common habit of putting things in their mouth will swallow the foreign body that might get stuck in the esophagus without being noticed by the parent. 3 Mirrors are commonly used for personal grooming or admiring one self (in which case the archaic term looking-glass is sometimes still used), decoration, and architecture. Glass of mirror are object that are rarely found in the case of foreign bodies impaction at esophagus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation